Sistem Informasi Absensi Mahasiswa Berbasis QR Code dan Firebase - Cindy; Darmeli Nasution; Dr. Leni Marlina (Jurnal Nasional Teknologi Komputer, 2026)
In today’s digital era, student attendance systems have become a crucial aspect of education management. This research aims to design and build a QR Code and Firebase-based student attendance information system at UNITAR Penang, Malaysia. This system is expected to improve efficiency and accuracy in the attendance process. The method used in this research is the Agile software development method, which allows for iterative and incremental development.